Unifying concepts in granular media and glasses - Coniglio, Antonio, 1940- (Elsevier, 2004)
Deep connections are emerging in the physics of non-thermal systems, such as granular media, and other "complex systems" such as glass formers, spin glasses, colloids or gels. This book discusses the unifying physical theories, developed in recent years, for the description of these systems. The special focus of the book is on recent important developments in the formulation of a Statistical Mechanics approach to granular media and the description of out-of-equilibrium dynamics, such as "jamming" phenomena, ubiquitous in these "complex systems". The book collects contributions from leading researchers in these fields, providing both an introduction, at a graduate level, to these rapidly developing subjects and featuring an up to date, self contained, presentation of theoretical and experimental developments for researchers in areas ranging from Chemistry, to Engineering and Physical Sciences. the book discusses very hot topics in physical sciences it includes contributions from the most prominent researchers in the area it is clearly written and self contained